Comparing green Machining and clean technology based Machining for tool wear reduction in Machining SAE 1045 steel. (2022) - Rajesh, S.; Saravanan, R.; Sekar, C.B.; Gnanavel, C.; Malladi, Avinash; Nagarathi, D.K.
Highlights: Waste coconut oil (WCCO) with Nanoparticles of Acidum Boricum to prepare machining coolant. Precision SAE 1045 Steel shaft machining application is focused in this application. Cost of coolant is minimized as well as use of waste coconut is promoted. Tool wear-based optimization carrier out with help of Taguchi Analysis. Abstract: The shafts of machines and motors are manufactured in Lathe and precision shaft machining requires costly cooling methods like Minimum Quantity Liquid coolant, cryogenic cooling or high-cost artificial coolant. On other hand some soft requires CNC machining for meeting the requirements. The machinability performance can be measured with respect to tool wear. If tool wear increases its affects surface quality. Here used coconut oil or waste coconut oil (WCCO) with Nanoparticles of Acidum Boricum for machining the precision shaft and measured tool wear responses to measure and optimize the machining performance. The conventional green machining and proposed nanofluid machining with proposed nanofluid performance compared. Taguchi L16 experimental deign employed with three factors varied at four levels. Cutting Vel. (40, 90, 140 and 190 m/min), Tool Feed (0.05, 0.10, 0.15 and 0.20 mm/rev) and The PVD coated insert used with Nose Radius (0.30, 0.60, 0.90 and 1.20 mm). The observation of both group of experiments statistically tested with independent samples test. The proposed method outperformed. Secondly the process parameters optimized with Taguchi analysis and further analyzed. Thirdly the mathematical model developed with ANOVA. This investigation focusses a passive technique of improving the flood cooling by use of biodegradable nanofluid as well as aimed to support the clean technology by identifying further use of WCCO.